Recognition and alleviation of pain in laboratory animals - Council, National Research; Studies, Division on Earth and Life; Research, Institute for Laboratory Animal; Animals, Committee on Recognition and Alleviation of Pain in Laboratory (National Academies Press, 2009)
The use of animals in research adheres to scientific and ethical principles that promote humane care and practice. Scientific advances in our understanding of animal physiology and behavior often require theories to be revised and standards of practice to be updated to improve laboratory animal welfare. Recognition and Alleviation of Pain in Laboratory Animals , the second of two reports revising the 1992 publication Recognition and Alleviation of Pain and Distress in Laboratory Animals from the Institute for Laboratory Animal Research (ILAR), focuses on pain experienced by animals used in research. This book aims to educate laboratory animal veterinarians; students, researchers and investigators; Institutional Animal Care and Use Committee members; and animal care staff and animal welfare officers on the current scientific and ethical issues associated with pain in laboratory animals. It evaluates pertinent scientific literature to generate practical and pragmatic guidelines for recognizing and alleviating pain in laboratory animals, focusing specifically on the following areas: physiology of pain in commonly used laboratory species; pharmacologic and non-pharmacologic principles to control pain; identification of humane endpoints; and principles for minimizing pain associated with experimental procedures. Finally, the report identifies areas in which further scientific investigation is needed to improve laboratory animal welfare.